2022
DOI: 10.1021/acs.orglett.2c00138
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV) Chloride-Catalyzed Photoalkylation via C(sp3)–H Bond Activation of Alkanes

Abstract: Despite the sophistication of C–H functionalization as one of the most powerful tools in organic synthesis, methodology for performing hydrogen-atom transfer of unactivated alkanes remains rather scarce. Herein, we describe chlorine radical-catalyzed C­(sp3)–H photoalkylation using titanium­(IV) chloride via a ligand-to-metal charge transfer process. Enabled by the unique properties of this abundant metal salt, the reaction not only effected the coupling of various alkanes with radical acceptors but also was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Very recently, Mitsunuma and Kanai [194] and the groups of Walsh and Schelter [195] simultaneously reported the Csp 3 À H alkylation of hydrocarbons catalyzed by Ti(IV) chlorides (Scheme 40). Analogously to the reactivity observed for Cu(II) or Fe(III) chlorides, this reactivity arises from the generation of Cl * via LMCT homolysis of Ti(IV)À Cl bonds.…”
Section: Reactions Mediated By Ti(iv) Complexesmentioning
confidence: 99%
“…Very recently, Mitsunuma and Kanai [194] and the groups of Walsh and Schelter [195] simultaneously reported the Csp 3 À H alkylation of hydrocarbons catalyzed by Ti(IV) chlorides (Scheme 40). Analogously to the reactivity observed for Cu(II) or Fe(III) chlorides, this reactivity arises from the generation of Cl * via LMCT homolysis of Ti(IV)À Cl bonds.…”
Section: Reactions Mediated By Ti(iv) Complexesmentioning
confidence: 99%
“…Since the metal cation did not affect the occurrence of the reactions, the electron transfer between the chloride ion (Cl − ) and the existing π-system Π , probably involving the sulfone or solvent, under 390 nm light was proposed to be the initial step. 11–17 This single electron oxidation produces the chlorine radical (Cl˙) and Π˙ − . Then, the efficient hydrogen atom abstraction using the chlorine radical (Cl˙) with 2a produced the cyclohexyl radical Int-A and regenerated the chloride ion and proton.…”
Section: Resultsmentioning
confidence: 99%
“…10–17 Compared with the classic homolysis of Cl 2 , the direct single electron oxidation of the chloride ion (Cl − ) is an ideal method for the generation of the chlorine radical. 11–17 Particularly, the dramatic developments in photocatalysis over the past decade have shed light on such a process, and a few strategies have been explored (Scheme 1-ii): (a) photoinduced ligand-to-metal charge transfer coupling with metal reduction and chloride oxidation; typically, metals with strong oxidative ability, such as Ni( iii ), 4 a ,12 Ti( iv ), 13 Ce( iv ), 6 a , b Fe( iii ), 14 and Cu( ii ), 15 are required; (b) single electron transfer between a chloride and a stochiometric amount of an oxidant, such as I 2 , O 2 , and O-radical, under photothermal conditions; however, these reactions suffer from drawbacks, namely, the need for strong oxidants and typical acidic conditions; 16 and (c) chloride oxidation by robust photocatalysts, such as Mes-Acr + ClO 4 − , (N-heteroarene)H + , and [Ir(dF(CF 3 )ppy) 2 (dtbbpy)]Cl. 17 These pioneering examples have shown the advantages of chlorine radical formation using chloride; however, a mild catalytic system avoiding the use of strong acids, oxidants, and photocatalysts is still highly required.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, titanium has been likewise reported to promote the generation of chlorine radicals via LMCT. In particular, Kanai and co‐workers found that the irradiation (λ=370 nm) of cheap and commercially available TiCl 4 in acetonitrile resulted in the formation of chlorine radicals [79] . The latter intermediates were used to cleave strong C(sp 3 )−H bonds and the resulting C‐centered radicals were employed for the hydroalkylation of electron‐poor olefins and ketones (Scheme 14A).…”
Section: Generation Of Halogen Radicals Via Lmct‐triggered Photolysismentioning
confidence: 99%
“…In particular, Kanai and co-workers found that the irradiation (λ = 370 nm) of cheap and commercially available TiCl 4 in acetonitrile resulted in the formation of chlorine radicals. [79] The latter intermediates were used to cleave strong C(sp 3 )À H bonds and the resulting Ccentered radicals were employed for the hydroalkylation of electron-poor olefins and ketones (Scheme 14A). Thus, when an acetonitrile solution of cyclohexane (14.1) and acetophenone (14.2) is irradiated with UV light, organoradical 14.4 * is generated and readily trapped by the carbonyl compound to afford alcohol 14.3 in 56 % yield after aqueous work-up.…”
Section: Titaniummentioning
confidence: 99%